Technical stability of autonomous control systems with variable structure - Matviichuk, K. S. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We obtain conditions for the technical stability of autonomous dynamical systems with discontinuous control with respect to a given measure.